Lacticaseibacillus rhamnosus alleviates intestinal inflammation and promotes microbiota-mediated protection against Salmonella fatal infections - Peng, Xianqi; Ed-Dra, Abdelaziz; Song, Yan; Elbediwi, Mohammed; Nambiar, Reshma B.; Zhou, Xiao; Yue, Min (Frontiers in Immunology, 2022)
Salmonella is a Gram-negative bacterium belonging to the Enterobacteriaceae family. It has been recognized as one of the most common pathogens causing gastroenteritis and systemic infections to chickens (1), resulting in a substantial economic loss to poultry industries (2-4). To date, at least 2,659 serovars have been described (5), where S. Gallinarum biovars Gallinarum and Pullorum have been considered the usual agents causing infections in chickens (4, 6-9). However, the implementation of successful programs has tackled the emergence of S. Gallinarum in poultry farms, especially in developed and some developing countries (10, 11). Nevertheless, recent surveillance studies have reported the involvement of non-host specific Salmonella serovars in many chicken infections, including serovars Typhimurium, Enteritidis, Thompson, and others (2, 12-14), which challenge efforts provided to ensure the safety of chicken herds.